Are Agroecosystem Services Under Threat? Examining the Influence of Climate Externalities on Ecosystem Stability - Temidayo Olowoyeye; Gideon Abegunrin; Mariusz Sojka (Atmosphere)
This study examines the impacts of climate-induced externalities on the stability of agroecosystems and the ecosystem services they provide. Using the PRISMA approach, we review literature published from 2015 to 2024. The study identifies how extreme weather events such as droughts, floods, heatwaves, and altered precipitation patterns disrupt the provisioning, regulating, and supporting services critical to food security, soil fertility, water purification, and biodiversity. Our findings show a continued increase in climate extremes, raising concerns about food security, environmental resilience, and socio-economic stability. It also reveals that regions dependent on rain-fed agriculture, such as parts of Africa, Asia, and the Mediterranean, are particularly vulnerable to these stressors. Adaptation strategies, including conservation agriculture, crop diversification, agroforestry, and improved water management, are identified as crucial for mitigating these impacts. This study emphasises the importance of proactive, policy-driven approaches to foster climate resilience, support agroecosystem productivity, and secure ecosystem services critical to human well-being and environmental health.